Analysis of Welding Current Variation Effects on Gas Metal Arc Welding (GMAW) Characteristics in Low-Carbon Steel - Irvan Bayu Irawan; Kurniawan; Ahmad Ruliyanto; Ikhwanul Qiram (Fakultas Teknik Universitas PGRI Banyuwangi, 2025)
This research utilizes Gas Metal Arc Welding (GMAW), a process whose performance characteristics significantly influence weld strength, particularly tensile capacity and flexibility. Higher electrical control contributes to increased tensile strength in welds, sometimes exceeding the base metal's tensile strength. However, during bend testing, lower electrical settings typically result in defects or cracks. Critical GMAW parameters power, voltage, and welding speed require precise adjustment to enhance weld quality. This study evaluates the impact strength of GMAW-welded steel using Charpy testing with 70° V-joints at currents of 90, 110, and 130 Amperes. The highest impact strength occurred at 110 Amperes, indicating optimal toughness, while 90 Amperes yielded low toughness. Fracture analysis revealed ductile fractures in 90-Amp specimens and mixed-mode fractures at 110/130 Amperes.